The Distribution of Salted Groundwater and the Impact to Settlement Areas in Grogol Sub District - Suharjo, S (Forum Geografi, 1991)
This research is aimed at studying the ground water salinity and the geographicaal aspect of Grogol subdistrict area. This study, therefore, dials withs (a) the ground water salinity and the factors influencing; (b) the classes of land suitability for settlement in Grogol subdistrict; and (c) the influences of the ground water salinity to the suitability of sattlement areas. This research put its emphasis on the geomorphological approach and uses lends units as the basis of its studt. The research area consists of four landform units and nine land units. From land unit maps, we can make the distribution maps of the ground water salinity and its influences to the suitability between settlement and the level suitability for settlement data. The ground water salinity data are obtained by measuring in the field and laboratory analysis. The result of this research shows that the distribution of the ground water salinity is located in the landform unit of the old floid and in the deposition processes. The distribution of the ground water salinity in the research area does not influence the growth pattern of settlement but influences the physical building.